Influence of oil palm replanting, age and management zones on soil carbon - Songkongon, Fadzilah; Mohd Amin, Adibah; Sim, C. Cheak; Sulaiman, Muhammad F. (Malaysian Society of Soil Science, 2022)
Oil palm (Elaeis guineensis Jacq.) cultivation is said to have caused losses of soil carbon due to deforestation. However, current oil palm cultivation is carried out either on previously rubber and cocoa plantation or replanted on first- or second-generation oil palm. The present study was conducted to assess whether there is a build-up of soil carbon throughout the growth of oil palm and will those amassed carbon (if any) be lost during replanting. The study was conducted at oil palm ages 5, 10, 15 years old, and newly replanted oil palm. At each age, soils were sampled at the frond heap pile (FH), the harvesting path (HP), and the inter-row (IR). Soil carbon content at all plots was not significantly different between ages with a mean of 2.24%. Between sections, soil carbon content at FH (3.10±1.42%) was significantly higher than the other sections. Our results showed that age of oil palm did not influence the accumulation of soil carbon. Replanting was also found not to have caused losses of soil carbon. As the different sections of the plantation yielded different results, future measurements of soil carbon should consider these different sections to properly represent the whole plantation.